Trade, global value chains and development - Dünhaupt, Petra,Herr, Hansjörg (Berlin School of Economics and Law, Institute for International Political Economy Berlin, 2020)
The catching-up of countries in the Global South to productivity levels and living standards of the Global North is the exception. There are two main economic explanations for this. First, developing countries are pushed to low-tech-labor-intensive productions and tasks in global value chains. This offers some advantages, for example easier industrialisation, but also prevents upgrading. Foreign direct investment only partially helps to overcome this problem. Second, low trust in national currencies in the Global South leads to distorted financial markets which do not provide sufficient credit for investment. As part of needed industrial policy, national development banks can play a key role in triggering the economic catching-up of the Global South. They can alleviate distortions in the financial system and at the same time support the transformation of the economy towards higher productivity and ecological transformation. The German development bank KfW can serve as a useful example of an effective development bank.
10419/221829
Keywords: Graue Literatur; Trade Theory; Economic Development; Global Value Chains; Industrial Policy; Financial Systems; Dollarisation; Development Banks